INNOVATION AND DIGITAL MARKETING STRATEGIES OF MSMES IN BAUBAU CITY TO ENHANCE COMPETITIVENESS IN THE MODERN ERA - Evi Trisetyasi; Yuyun Iriani; Zahwa Nur Syahda (MESP–FEB UNS, 2026)
Although micro, small, and medium enterprises (MSMEs) play a crucial role in regional economic development, many MSMEs in Baubau City still operate conventionally and have not yet optimally utilized digital technology. This study examines innovation, digital marketing strategies, and the supporting and inhibiting factors faced by MSMEs in Baubau City to increase their competitiveness. A descriptive qualitative method was used. Data were collected through in-depth interviews with five purposively selected MSME informants, supplemented by field observations and documentation. Data analysis was conducted according to the Miles et al. (1994) model, which consists of data reduction, data presentation, and drawing conclusions. MSMEs in Baubau City utilize digital-based product, packaging, and service innovations. This includes online ordering and cashless payments. For promotion, sales, and customer interaction, digital marketing strategies utilize platforms such as Instagram, Facebook, TikTok, Shopee, and WhatsApp Business. However, the level of utilization varies among informants. Supporting factors include available technology, high consumer interest in local products, and government-facilitated digital training. Inhibiting factors include limited knowledge of digital marketing, limited capital, inability to create engaging content, and increasingly fierce market competition. This study adds to the MSME literature by providing empirical evidence from Eastern Indonesia that the synergy between innovation and digital marketing is a key mechanism for building competitive advantage. This research differs from previous studies that consider each of these elements separately. Instead, it demonstrates how these elements contribute to the digital transformation of the regional economy. It includes small businesses in underserved areas through the Resource-Based View and Dynamic Capabilities framework.